A study of dust structure nearby white dwarf WD1334-678 - Joshi, Ishwor Nath; Jha, A. K.; Aryal, B. (BIBECHANA, 2021)
A low flux density region nearby white dwarf WD1334-678  in the 140 µm AKARI survey maps has been systematically searched and found a far-infrared cavity centered at R.A. (J2000) = 13h38m14.4s, Dec.(J2000) = −68◦40’42”, in which minimum flux is 19.5 MJy/sr at 90 µm wavelength. The physical properties (Size, dust color temperature, dust mass) and thermodynamic property (Planck function distribution) of the cavity using 140 µm and 90 µm AKARI survey data. The size of the cavity is found to be 0.17◦× 0.12◦ has been presented. The dust color temperature is found in the range 17.70 ± 0.01 K to 18.81 ± 0.01 K. The Plank function distribution along major and minor diameters shows a very good agreement with sinusoidal fitting. The period of oscillation of dust particles along major and minor diameters are 3.2 Wm-2Sr-1Hz-1arcmin-1and 1.6 Wm-2Sr-1Hz-1arcmin-1, respectively.BIBECHANA 18 (2) (2021) 130-137